Influencing factors and mechanisms promoting proactive health behavior intention: an integration of the health belief model and the theory of planned behavior - Fang, Lidong; Zhang, Qiaoqiao; Zhou, Ning; Chen, Jin; Lou, Hu (Frontiers in Public Health, 2025)
BackgroundPromoting proactive health behaviors is an effective strategy for addressing public health challenges and advancing the “Healthy China” initiative. This study aims to explore the driving factors and mechanisms influencing proactive health behavior intention by integrating the theory of planned behavior (TPB) and the health belief model (HBM).MethodsA cross-sectional survey design was employed. A structured questionnaire was developed based on the theory of planned behavior (TPB) and the health belief model (HBM), covering eight dimensions: health behavior attitude, subjective norms, perceived behavioral control, self-efficacy, perceived susceptibility, perceived severity, perceived benefits, and perceived barriers. A total of 462 valid responses were collected using convenience sampling at a hospital health examination center in Jiangsu Province, China. Participants were approached on-site during routine check-ups and voluntarily completed the survey after providing informed consent. Data were analyzed using SPSS 26.0 and AMOS 26.0. Reliability and validity were tested using Confirmatory Factor Analysis (CFA), and hypotheses were examined through Structural Equation Modeling (SEM).ResultsThe findings revealed that perceived susceptibility, severity, benefits, and barriers significantly influenced individuals’ attitudes toward health behaviors. Attitudes, subjective norms, and perceived behavioral control significantly predicted intention, with self-efficacy partially mediating these effects. Perceived barriers had a negative effect, suggesting practical challenges hinder the development of health intentions.ConclusionHealth belief factors, especially perceived benefits, significantly influence health behavior attitude. TPB variables—particularly attitude—are key predictors of proactive health behavior intention. Self-efficacy acts as an important mediator, enhancing the explanatory power of the integrated TPB-HBM model. These findings provide theoretical and practical guidance for designing interventions to promote proactive health behavior in the general population.